Optimizing Transportation Project Design and Management: The Impact of Building Information Modeling (BIM) Implementation at Delta Construction Company Ltd. in Vietnam - Vu Duc Hung Phu (International Journal of Scientific Research in Civil Engineering, 2024)
The primary objective of this study is to assess the application and effectiveness of Building Information Modeling (BIM) in the design and management of transportation projects, focusing specifically on Delta Construction Company Ltd. This research aims to explore how BIM influences project outcomes, including design accuracy, cost efficiency, and project timelines, particularly within the context of the Vietnamese construction industry. To achieve this, a mixed-methods approach was employed, combining quantitative data from surveys of employees and experts with qualitative insights from in-depth interviews. The results reveal that the implementation of BIM has led to significant improvements in both the design process and project management at Delta Construction Company Ltd. Specifically, the use of BIM has reduced design time by an average of 15% to 20% and has enhanced project management by providing more accurate tools for monitoring progress and quality control. These findings underscore the potential of BIM to optimize construction processes and improve overall project outcomes. However, the study also identifies challenges related to software integration and the need for comprehensive training to fully realize BIM’s benefits. The conclusions drawn from this research suggest that with continued investment in training and better integration of BIM systems, companies in Vietnam can significantly enhance their project efficiency and quality, contributing to the sustainable development of the construction industry.
Keywords: Building Information Modeling; Transportation Project Design; Project Management; Construction Industry In Vietnam; Technological Integration